How to maximize performance during Paralympics by analyzing the Human-wheelchair-athletic track interactions ? - Michel, M.; Loubet, J. L.; Mazuyer, D. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Sciences2024 is a collaborative French research project between sport federations and academic researchers aimed at improving athletics and para-athletics performance for the Paris Olympic and Paralympic Games. Thus, for instance, maximizing the velocity of the wheelchairs during competitions requires to increase the grip between gloves and handrims during the propulsion phase as well as to understand the friction dissipation between the wheelchair tire and the athletic track during the rolling phase.